Quality and Promotion Analysis of Members' Decisions in Applying for Musyarakah Financing at KKS Kencong - Isnaini, Nandita Febri; Mu’awwanah, Uliyatul (Institut Agama Islam Sunan Giri Ponorogo, 2024)
In business, many things must be considered regarding operations, marketing, and services, including the world of financial institutions, both Sharia and conventional. KKS Nur Indah Abadi is a Sharia Cooperative that is growing rapidly. Of course, establishing the Nur Indah Abadi Kencong KKS will attract members and improve member policies by understanding members' hopes and needs. This research aims to determine the influence and analyze quality and promotion on the decisions of Nur Indah Abadi Kencong KKS members. This research has three independent variables: promotion quality variables X1 and X2, and one dependent variable, the member decision variable. The data analysis method in this research uses multiple regression analysis. The primary data collection tool used a questionnaire distributed to Nur Indah Abadi Kencong KKS members in this study, totaling 45 respondents. The high correlation coefficient shows that improving product quality and promotions strongly contributes to increasing member decisions in musyarakah financing at KKS (Consumer Sharia) Nur Indah Abadi Kencong. The research results show that partial quality and promotion positively and significantly affect member decisions.